Entre teares e lutas: relações de gênero e questões etárias nas principais fábricas de tecidos do Distrito Federal (1891 - 1932) - Pires, Isabelle Cristina da Silva (2018)
This study tries to focus on gender relations and age issues among workers who worked in the main textile mills of the Federal District between 1891 and 1930. The textile industry, in this period, employed considerable labor of women and children, considering them as possessing important characteristicsto dealing with the raw material and machinery, such as delicacy, patience, flexibility, smallness, etc. However, through the speeches of militant workers, we noticed that some workers felt threatened and troubled by the presence of the female and child labor force because they believed that they lowered wages and were passive before their exploitations, which would weaken the protest movements. Looking to problematize this perspective, this research seeks to portray women and children as subjects of their own history, aware of the explorations to which they were subjected and active agents in strikes and protests for better living and working conditions. For the bosses, female and child labor was interesting and they deployed social services in an attempt to keep women in factories after marriage and children even against the public power. The sexual division of labor and the factory discipline demarcated spaces, behaviors and established a hierarchy based on notions of "qualification". However, the workers sought to resist before forms of control and fought for their demands inside and outside the factories.